MENINGKATKAN PRESTASI BELAJAR SEJARAH MELALUI MODEL PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) PADA SISWA KELAS XI SMA NEGERI 5 PALU - Latief, Juraid Abdul (Katalogis, 2017)
Problems in this research is how to improve student achievement through cooperative learning method of Student Teams-Achievement Divisions (STAD) type in XI IPS3 students in SMA Negeri 5? The purpose of this study is To improve student learning achievement through STAD model on the students of class X in SMA Negeri 5 Palu year 2016/2017 lesson. In addition, it is expected that history teachers can use STAD learning model as one of alternative choice in learning history. The use of learning models that have a cooperative element so that the results of learning can evenly the results. Historical teachers should always give a positive attitude or appreciation to each student activity on the learning process of history, because it can trigger students to always learn hard. This research belongs to a classroom action research. Research location in SMA Negeri 5 Palu. Data collection techniques in this study using several techniques that are (1) observation, (2) documentation, (3)end test cycle. The analysis is done by analyzing the mean of class value, the learning completeness classically, the result of student activity observation, and the result of questionnaire about students. The results of this study indicate that the use of STAD type cooperative learning model can improve student learning activities better in students and teachers as well as improve student achievement and learning outcomes class XI IPS 3 SMA Negeri 5 Palu. Student learning outcomes before the application of STAD learning model obtained the average value of class 63.67 with the percentage of classical completeness of 43.33%. In cycle I after held a class action research with the application of STAD learning model obtained an average value of 65 with 50% complete percentage of mastery. In the first cycle, the average grade and completeness of classical learning has increased, but it has not reached the success indicator. Next cycle II and obtained data that is the average grade of 81.67 with classical completeness reached 86.67%. In the second cycle there is an increase and already meet the success indicator of 80% classical learning completeness.